Internalisasi Nilai-Nilai Pendidikan Islam pada Ritual 1 Muharram di Dusun Limbangan Desa Giyono Kecamatan Jumo Kabupaten Temanggung - Dwi Rachmat Setiyono; Nurul Mubin; Sofan Rizqi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This research seeks to investigate and analyze how the 1 Muharram ceremony in Limbangan Hamlet, Giyono Village, Jumo District, Temanggung Regency, imparts Islamic educational principles. The 1st of Muharram ritual, which is usually commemorated with various religious activities and local traditions, is considered an important moment to reflect and strengthen Islamic teachings in society. Based on observations and interviews with local residents, this research found that in each series of activities, such as group prayer, reciting shalawat, and the tradition of eating together, Islamic educational values are contained which include morals, brotherhood, sincerity, and social concern. The internalization of these values is not only carried out at the ritual level, as well as in the residents of Limbangan Hamlet's day-to-day lives, where they exhibit traits like being respectful of one another and sticking together. This research finds that the 1 Muharram ritual in Limbangan Hamlet serves multiple purposes. Firstly, it commemorates the Islamic New Year. Secondly, it helps build the Muslim community's identity by teaching the younger generation the values of Islamic education.